Identification of plasma protein panels for detection of cognitive decline in MCI and AD by LC‐MS/MS. (31st December 2021) - Inoue, Makoto; Ito, Hitomi; Liu, Shan; Suzuki, Hideaki; Akatsu, Hiroyasu; Matsukawa, Noriyuki; Asada, Takashi; Arai, Tetsuaki; Uchida, Kazuhiko
Abstract: Background: For the prevention of dementia, noninvasive screening methods which detect the signs of cognitive decline before clinical symptom occurs are needed. We previously reported blood‐based composite marker for mild cognitive impairment (MCI) and Alzheimer's disease (AD) consisting of apoA1, TTR, and C3. A combination of blood proteins could be a promising biomarker for monitoring the progression of cognitive decline from early stages of the disease. Here, we developed LC‐MS/MS‐based blood test using plasma proteins for MCI and AD to explore accurate and practical screening of the disease. Method: We constructed a robust and reproducible LC‐MS/MS blood test system equipped with MRM to quantify 45 major plasma proteins with relatively high amounts using isotope‐labeled synthetic peptide. These plasma protein levels from 192 cases (NDC: 58, MCI: 71, AD: 63) were determined. Multinomial regression and ROC analyses were performed to identify the combination of the plasma protein panels that could discriminate NDC vs. MCI and/or AD. Result: We found eight interpretable protein biomarker candidates in plasma for MCI and AD, which were related to innate immunity, coagulation pathways, lipid metabolism, and nutrition. Some of them are involved in the neurovascular unit injury. The optimal combination of these proteins and the coefficients of the logistic models revealed different clinical potential between male and female. In the model discriminating cognitive impairment from NDC, the AUC values of the ROC analysis were 0.82 and 0.72 for male and female, respectively. Furthermore, we constructed composite scores optimized for male and female using these plasma protein panels, and they had a significant correlation with severity of the cognitive decline determined by clinical manifestation. Conclusion: LC‐MS‐based plasma protein panels interpretable for pathophysiology of AD detect signs of cognitive decline and progression of the disease.